Porcine Bladder Urothelial, Myofibroblast, and Detrusor Muscle Cells: Characterization and ATP Release - Cheng, Ying; Mansfield, Kylie; Sandow, Shaun; Sadananda, Prajni; Burcher, Elizabeth; Moore, Kate (Frontiers in Pharmacology, 2011)
ATP is released from the bladder mucosa in response to stretch, but the cell types responsible are unclear. Our aim was to isolate and characterise individual populations of urothelial, myofibroblast and detrusor muscle cells in culture, and to examine agonist-stimulated ATP release. Using female pig bladders, urothelial cells were isolated from bladder mucosa following trypsin-digestion of the luminal surface. The underlying myofibroblast layer was dissected, minced, digested and cultured until confluent (10-14 days). A similar protocol was used for muscle cells. Cultures were used for immunocytochemical staining and/or ATP release investigations. In urothelial cultures, immunoreactivity was present for the cytokeratin marker AE1/AE3 but not the contractile protein α-smooth muscle actin (α-SMA) or the cytoskeletal filament vimentin. Neither myofibroblast nor muscle cell cultures stained for AE1/AE3. Myofibroblast cultures partially stained for α-SMA, whereas muscle cultures were 100% stained. Both myofibroblast and muscle stained for vimentin, however, they were morphologically distinct. Ultrastructural studies verified that the suburothelial layer of pig bladder contained abundant myofibroblasts, characterised by high densities of rough endoplasmic reticulum. Baseline ATP release was higher in urothelial and myofibroblast cultures, compared with muscle. ATP release was significantly stimulated by stretch in all three cell populations. Only urothelial cells released ATP in response to acid, and only muscle cells were stimulated by capsaicin. Tachykinins had no effect on ATP release. In conclusion, we have established a method for culture of three cell populations from porcine bladder, a well-known human bladder model, and shown that these are distinct morphologically, immunologically and pharmacologically.